Auditory–Visual stimuli: Effects on derived relations with compound stimuli. (10th November 2020) - Guerrero, María Soledad; Maldonado, Miguel Ángel; Moriana, Juan Antonio; Alós, Francisco J.
Abstract: This research explored the effect of teaching conditional discriminations with three procedures on the derivation of 36 stimuli relations (derived relations). The stimuli used consisted of three characteristics musical instruments, along with the corresponding picture. In the first experiment six university students were trained with simple stimuli and tested with compound auditory–visual samples; therefore, a one‐to‐many structure was used. In the second experiment, auditory stimuli were replaced by visual stimuli, for the samples used, for new students. A third experiment was implemented with an extra phase of training with compound stimuli for six new students. The structure of the experiments was: pretests (Xbcd–A; Xacd–B; Xabd–C; Xabc–D), training (A–B; A–C; A–D), and posttests (same as pretests). The difference between these conditions was the kind of stimuli used and a new phase of teaching used in condition 3: (Xbcd–A). The results indicate that training with simple stimuli on discriminations that include stimuli that are easy to discriminate from each other (words and sounds) is a sufficient condition for good posttest performance. However, when comparisons are made difficult (words only), participants show better performance on new tests if they have a learning history with compound stimuli.